2018
DOI: 10.1007/s00198-018-4473-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of fractures among patients with rheumatoid arthritis: a systematic review and meta-analysis

Abstract: Patients with RA are at high risk of incident overall and fragility fractures. Consideration of vertebral imaging for patients with additional OP risk factors, including RA-specific risk factors, may help with early OP diagnosis and timely intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…Also, due to the lack of data about trauma level, some of the traumatic fractures might be misclassified as osteoporotic fractures. Despite that, our fracture incidence rates were comparable to the reported rates in a recent meta-analysis of 25 cohort studies in patients with RA (pooled incidence rates of fragility fractures 15.31 (95% CI 10.43 to 22.47) per 1000 person-years) 48. Additionally, the majority of the vertebral fractures are not clinically recognisable at early stages, and the diagnosis of these fractures requires ≥2 radiographic assessments at appropriate intervals.…”
Section: Discussionsupporting
confidence: 80%
“…Also, due to the lack of data about trauma level, some of the traumatic fractures might be misclassified as osteoporotic fractures. Despite that, our fracture incidence rates were comparable to the reported rates in a recent meta-analysis of 25 cohort studies in patients with RA (pooled incidence rates of fragility fractures 15.31 (95% CI 10.43 to 22.47) per 1000 person-years) 48. Additionally, the majority of the vertebral fractures are not clinically recognisable at early stages, and the diagnosis of these fractures requires ≥2 radiographic assessments at appropriate intervals.…”
Section: Discussionsupporting
confidence: 80%
“…Our study only shows the osteoporosis site fracture incidence in patients with RA. As we indicated in our manuscript, the incidence rate of osteoporotic fractures in our cohort is similar to a recent meta-analysis of 25 cohort studies in patients with RA 3…”
supporting
confidence: 90%
“…A recent systematic review and meta-analysis not only confirmed this result, but also conducted site-specific analyses in RA patients on fractures in the vertebrae, hip, forearm, and proximal humerus. Incidence rates were found to be highest in the vertebrae, leading the authors to suggest vertebral imaging specifically in these patients to assess clinical deterioration of bone structure in the spine, in addition to assessment of other known osteoporotic risk factors, including those specific to RA [ 25 ]. This is consistent with previous data, demonstrating vertebral facture rates in RA to be as high as twice the expected value in the general population [ 26 ].…”
Section: Discussionmentioning
confidence: 99%